Effect of BaO on physical, optical and structural characteristics of ZnO Al2O3 B2O3 glasses - Saudi, H. A. (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Zinc barium borate glasses with composition (65-x) B2O3-10Na2O-10Al2O3-10ZnO-5Li2O-xBaO with (0 â‰¤ x â‰¤40 % mol) have been prepared using melt quenching technique. The density, molar volume and the optical absorption studies revealed that the optical band gap energy (Eopt) and Urbach energy increase with the increase of BaOcontent.This is mainly due to the increased polarization of theBa2+ ions and the enhanced formation of non-bridging oxygen (NBO). The IR studies indicate that these glasses are made up of [AlO6], [BO3],[BO4], and [AlO4] basic structural units.